Evocation - Gibson, S. T. (Summoner's circle, 2024)
"The day David Aristarkhov's occultist father died, he bought himself an Audi, drank every drop of liquor in the house, and abandoned his life as a teen psychic prodigy. Now pushing thirty, David is a Boston attorney, moonlighting as a medium for a secret society. But when the Devil comes to collect on a deal David's ancestor made, he reluctantly reaches out to his ex-boyfriend Rhys for help. However, to get to Rhys, David will have to befriend Moira, Rhys's wife. The trio gets a little too close for comfort as they combine their powers to unravel the century-old curse, and if they don't break the curse by David's thirtieth birthday, he won't live long enough for everyone to figure out their feelings for each other"--